Pigment-Dispersing Factor-expressing neurons convey circadian information in the honey bee brain. Issue 1 (10th January 2018) - Beer, Katharina; Kolbe, Esther; Kahana, Noa B.; Yayon, Nadav; Weiss, Ron; Menegazzi, Pamela; Bloch, Guy; Helfrich-Förster, Charlotte
Abstract : Abstract : Pigment-Dispersing Factor (PDF) is an important neuropeptide in the brain circadian network of Drosophila and other insects, but its role in bees in which the circadian clock influences complex behaviour is not well understood. We combined high-resolution neuroanatomical characterizations, quantification of PDF levels over the day and brain injections of synthetic PDF peptide to study the role of PDF in the honey bee Apis mellifera . We show that PDF co-localizes with the clock protein Period (PER) in a cluster of laterally located neurons and that the widespread arborizations of these PER/PDF neurons are in close vicinity to other PER-positive cells (neurons and glia). PDF-immunostaining intensity oscillates in a diurnal and circadian manner with possible influences for age or worker task on synchrony of oscillations in different brain areas. Finally, PDF injection into the area between optic lobes and the central brain at the end of the subjective day produced a consistent trend of phase-delayed circadian rhythms in locomotor activity. Altogether, these results are consistent with the hypothesis that PDF is a neuromodulator that conveys circadian information from pacemaker cells to brain centres involved in diverse functions including locomotion, time memory and sun-compass orientation.